Investigate the role of of Human Error in non-fatal accidents drivers the province of Yazd - Gh Halvani; P azad; S zakyan; R Soltani Gerdefaramarzi; B Kouhnavard (طب کار)
Introduction: human factor, road, vehicle and environment are factors that impact on driving road. One of the important statistics about accidents and injuries consensus on the role of human factors in 90-70 percent of all accidents. The purpose of this study was to investigate the role of human error in accidents in driver's terminals once the province of Yazd. Methods: This Cross-sectional study was carried out in 2013 among the drivers of transport terminals in Yazd city.The number of cases was 300 people that were selected by random method. A multi-part questionnaire including demographic characteristics, data related of drivering and Driver Behavior Questionnaire (DBQ) were applied. Results: The unintentional violations that were caused by the careless and lightheadedness was down that represents the good culture of the community to be studied. The relationship between the rate of speed when driving in a landslide was a significant correlation (03/0, 04 / 0P <). Also among the items age, work experience, type of certification, the amount of kilometers of driving per week and per year, and average and maximum speed of the car with the infringers, significant relationships were found. Conclusion: The main result this study was that a large number of drivers do not show necessity for committing violations and Most of violations was deliberately accuracy